(+76)-(-7)=

Simple and best practice solution for (+76)-(-7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (+76)-(-7)= equation:


(+76)-(-7)=0

We simplify the equation to the form, which is simple to understand
(+76)-(-7)=0

Remove unnecessary parentheses
+76-(-7)=0

Remove unnecessary parentheses
+76+7=0

We move all terms containing to the left and all other terms to the right.
0=0-76-7

We simplify left and right side of the equation.
0=-83

0=-83

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| B/4=15.5 | | 150+77x=240+54x | | -9b-7+3b=11 | | -2b=58 | | 134=-4x-2(4x-7) | | -6x+8=-2+2 | | -5/7+1/3 | | 5.6/0.4-r=8 | | 3x-1=3(x-1) | | 5t=6t+7 | | 599-5(21+20)=y | | 5(x+2)-3=12 | | 455=180+3x+1.5x | | 14+8x=-x-5 | | 4x^3-10x^2-64x+160=0 | | -3x+2x=5 | | -6=X+39/-9 | | 6x^2+5x=o | | 2-6(6+2k)=-106 | | -5r-(42+14r)=-99 | | 4x^3-10x^2-64+160=0 | | 163=-7x+3(7x+17) | | 9/3*3+7-3=y | | 3.5p=39.5 | | 2(4x+1)=4x-6 | | 8x-11=13+8u | | 3(x+2)-3x=12 | | 83=-5x+3(-3x-5) | | (3/7)*p=48 | | 1.4h=1.8h+4.8-.4h | | 4+-22= | | (X+2)+(2x+2x)=4x+x |

Equations solver categories